Українська підляська говірка в поезії Юстини Королько: фонетичний рівень - Яворський, Андрій Юрійович; Yavorskij, A. Yu. (Східноєвропейський національний університет імені Лесі Українки, 2014)
У творах поетеси з Північного Підляшшя (Польща) Юстини Королько проаналізовано фонетичні особливості місцевої української говірки, зокрема прокоментовано специфіку рефлексації давніх голосних, відмінності у вживанні приголосних, комбінаторні звукові зміни. З’ясовано специфіку використання авторкою діалектних елементів. Phonetics of Podlasie dialects, including specificity of long vowels relaxation, particularity of consonants depalatalization, differences in the frequency of certain consonants usage and effects of combinatorial sound change are fully and systematically reflected in the works of Ukrainian poet from the North Podlasie (Poland) Justine Korolko. The phonetic level phenomena allowed to qualify the dialect used in the texts as an archaic North Ukrainian. J. Korolko not only attempted to use certain dialect elements or imitation of dialect speech. Her works are written in Podlasie dialect, which essentially serves as a literary language. The texts fully represent the North Podlasie Ukrainian dialects and can be successfully used as a material for dialectological studies.
Ukrainian Podlasie dialect in Justine Korolko’s poetry: phonetic level
Keywords: підляські говірки; голосні фонеми; рефлекси давніх голосних; дифтонги; монофтонги; приголосні фонеми; Podlasie dialects; vowel phonemes; long vowels reflexes; diphthongs; monofthongs; consonant phonemes